2008
DOI: 10.1016/j.ijhydene.2007.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental validation of a hydrogen storage tank with metal hydrides

Abstract: This paper presents a hydrogen storage system using metal hydrides for a combined heat and power (CHP) system. Hydride storage technology has been chosen due to project specifications: high volumetric capacity, low pressures (< 3.5 bar) and low temperatures (< 75 • C: fuel cell temperature). During absorption, heat from hydride generation is dissipated by fluid circulation. An integrated plate-fin type heat exchanger has been designed to obtain good compacity and to reach high absorption/desorption rates. At f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 7 publications
(6 reference statements)
0
30
0
Order By: Relevance
“…The model developed here is similar to these others in its physics, but accels due to the Simulink environment, in its ability to be easily integrated into complex system models. Integration of hydrogen storage models into larger system models is becoming more important as metal hydride applications become more widespread [11]. Additionally, the experimental work reported in the literature generally centers on purpose built, ideal, experimental hydride reaction beds cooled by integrated cooling systems [1,7,8].…”
Section: Background and Motivationmentioning
confidence: 99%
“…The model developed here is similar to these others in its physics, but accels due to the Simulink environment, in its ability to be easily integrated into complex system models. Integration of hydrogen storage models into larger system models is becoming more important as metal hydride applications become more widespread [11]. Additionally, the experimental work reported in the literature generally centers on purpose built, ideal, experimental hydride reaction beds cooled by integrated cooling systems [1,7,8].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Kaplan et al [2] presented a mathematical model for hydrogen storage in a metal hydride bed; the team concluded that a rapid charge needs efficient cooling. Muthukumar et al [3][4][5][6][7][8][9] made a parametric investigation of a metal hydride hydrogen storage device, they showed that overall increasing heat transfer coefficient is not beneficial. Phate et al [4] carried out a computational analysis of a cylindrical metal hydride bed; their conclusion is that the concentration gradient in the bed is the major driving force of hydrogen flow in the bed.…”
Section: Introductionmentioning
confidence: 99%
“…Phate et al [4] carried out a computational analysis of a cylindrical metal hydride bed; their conclusion is that the concentration gradient in the bed is the major driving force of hydrogen flow in the bed. Marty et al [5][6][7][8][9][10][11][12][13][14] added an experimental validation to the computational simulations of the hydrogen storage tank with metal hydrides; their goal was to obtain performances according to the objectives imposed by a stationary cogeneration system. Askri et al [6] made a numerical investigation of heat and mass transfer of a 3D annular tank.…”
Section: Introductionmentioning
confidence: 99%
“…To reach these targets, various simulation and experimental methods have been investigated using distinctive hydrogen storage materials and heat exchanger designs [3][4][5][6][7][8]. In a previous work done by Milan Visaria et al [3], a two-dimensional prototype of heat exchanger in a Ti 1.1 CrMn metal hydride tank is proposed, where the temperature, reaction completion, and volumetric heat generation over time is recorded.…”
Section: Introductionmentioning
confidence: 99%